2018
DOI: 10.1371/journal.pone.0206634
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bacterial growth conditions from mRNA and protein abundances

Abstract: Cells respond to changing nutrient availability and external stresses by altering the expression of individual genes. Condition-specific gene expression patterns may thus provide a promising and low-cost route to quantifying the presence of various small molecules, toxins, or species-interactions in natural environments. However, whether gene expression signatures alone can predict individual environmental growth conditions remains an open question. Here, we used machine learning to predict 16 closely-related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…These findings could indicate that for these reactions, the fluxes are controlled at the gene expression level [53] . However, other works found that a combination of both omics yields slightly better results [54] , while others point to higher predictive power from proteomics data [55] , [56] . In essence, it seems that the two omics contain relevant information for metabolic modeling and it would probably be best to use a combination of both in order to maximize the amount of available information.…”
Section: Discussionmentioning
confidence: 95%
“…These findings could indicate that for these reactions, the fluxes are controlled at the gene expression level [53] . However, other works found that a combination of both omics yields slightly better results [54] , while others point to higher predictive power from proteomics data [55] , [56] . In essence, it seems that the two omics contain relevant information for metabolic modeling and it would probably be best to use a combination of both in order to maximize the amount of available information.…”
Section: Discussionmentioning
confidence: 95%
“…Next, by evaluating the accuracy, the model's hyperparameters can be tuned to improve its generalization performance for unseen data. [ 101,102 ] The model can be retrained after finding the best hyperparameters. Figure 4 shows how evaluation methods can help to improve the model's performance.…”
Section: Ml: a Data‐driven Approachmentioning
confidence: 99%
“…When k-fold cross-validation is operated, one can see how sensitive the model is to the training dataset. Next, by evaluating the accuracy, the model's parameters can be tuned to improve its generalization performance for unseen data [89,90]. The final evaluation of the model is conducted with test data, and the predictive ability of the model is quantified by different evaluation metrics such as accuracy, sensitivity, specificity, precision, and recall [91,92].…”
Section: Validation and Evaluationmentioning
confidence: 99%